COMPARATIVE STUDY ON THE ENERGY POLICIES FOR BUILDING SECTOR IN ALGERIA AND FRANCE, IN ORDRE TO IMPROVE OUR POLICY - Meftah, N; Mahri, Z L (university of el oued/جامعة الوادي, 2021)
Energy policy plays an important role in confronting the energy crisis, in particular in the buildings sector which is responsible for 40% of consumption in Algeria and 42% in France, in Algeria the building sector is in full expansion following an accumulated delay of Several decades of lack of housing, committed to an energy policy will allow the preservation of natural resources, in France the objective and reduce their energy dependence and energy bill and allow the money saved to finance other projects and economic activities , it would be useful to compare the energy policies of Algeria and France to find the strengths and weaknesses of each policy,based on the comparison, recommendations were made to improve our policy and tackle barriers to achieve our goals.
Article
Keywords: Efficiency in buildings; building energy management; energy audit; building performance simulation, energy policy.